Application of photogrammetry for mapping of solution collapse breccia pipes on the Colorado Plateau, USA. (14th December 2017) - Klawitter, Matthias; Pistellato, Davide; Webster, Anthony; Esterle, Joan
Abstract: Solution collapse breccia pipes (SCBPs), that form under the influence of gravity, and sinkholes were studied on the Colorado Plateau in Arizona, USA to identify preserved evidence of their formation mechanisms. Close range photogrammetry was employed for data acquisition and reconstruction of the three‐dimensional (3D) scene of the outcrops. Key geological features were accurately mapped within their true 3D space using photogrammetry. Interpretations of the results suggest that the mechanisms controlling the collapse, and its debris distribution within the pipe, are influenced by in situ discontinuities in the host rocks at every scale from the regional context to the size and shape of the collapsed blocks.